MODEL PENYULUHAN KB BERBASIS GENDER DALAM MENCEGAH KEKERASAN DALAM RUMAH TANGGA DI KABUPATEN PURBALINGGA - Dyah Retna Puspita; Rin Rostikawati; Lilis SS (Faculty of Law, Universitas Jenderal Soedirman, 2014)
This study was conducted in Purbalingga which has a lot of hair manufacturing company which are predominantly done by women. The aims of this research were: (1) to analyze the phenomena of shifting of gender role in labor families, (2) to analyze the implementation of family planning counseling as a prevention of domestic violence, and (3) to create a gender-based family planning model to prevent it. The result shows that (1) there is a shifting of gender role in research location, (2) the activity of domestic violence counseling was rarely implemented, and (3) revitalization of those counseling model involving strategy, target and counseling materials need to be implemented.Key words: family planning extension shifting gender role, domestic violence and dissemination on gender basic.